Interstitial lung involvement in rheumatoid arthritis - David Vladimirovich Bestaev; T. D. Bestaeva (Современная ревматология)
Rheumatoid arthritis (RA) is a systemic autoimmune rheumatic disease of unknown etiology, characterized by chronic erosive arthritis and extraarticular manifestations. Pulmonary involvement is one of the common extraarticular manifestations of RA and may show itself as bronchial tree lesions, rheumatoid nodules, Caplan's syndrome, and lesions in the pleura or pulmonary interstitium (interstitial lung involvement (ILI)). High-resolution computed tomography allows the diagnosis of ILI in RA in nearly 70% of cases although the incidence of ILI may be lower (4 to 30%) depending on diagnostic methods and patient selection criteria. There are several histopathological types of ILI, the differential diagnosis of which can be troublesome. Usual interstitial pneumonia (UIP) and nonspecific interstitial pneumonia are major types of RA-associated ILI. UIP-pattern ILI has a more severe course than ILI with other histological patterns. The clinical presentation of ILI may be complicated by the likely toxic effect of a number of disease-modifying antirheumatic drugs (DMARDs) used to treat RA, such as methotrexate and leflunomide, and biological agents (BAs), tumor necrosis factor-α (TNF-α) inhibitors. The pathogenesis of pulmonary involvement in RA and the role of synthetic DMARDs and BAs in the development of ILI call for further investigations.An extraarticular manifestation, such as ILI, affects the choice of treatment policy in patients with RA.The relevance of a study of ILI is beyond question. The paper discusses the state-of-the-art of investigations in this area.